2015
DOI: 10.1016/j.fob.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate (EGCG) suppresses lipopolysaccharide‐induced inflammatory bone resorption, and protects against alveolar bone loss in mice

Abstract: HighlightsWe examine the role of EGCG, a major polyphenol in green tea, in bone metabolism.LPS is a pathogen-associated molecule, and induces inflammatory bone resorption.EGCG suppresses the LPS-induced PGE production in osteoblasts.EGCG suppresses the LPS-induced bone resorption of alveolar bones in vitro.In the mouse model of periodontitis, EGCG restores the loss of alveolar bone mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…1). In our previous study, the treatment of 30-90 lM EGCG dose dependently suppressed LPSinduced bone resorption [15], but 3-10 lM EGCG3″ Me clearly suppressed the bone resorption in the present study. Therefore, the inhibitory potency of EGCG3″Me seems to be slightly stronger than that of EGCG in bone resorption.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…1). In our previous study, the treatment of 30-90 lM EGCG dose dependently suppressed LPSinduced bone resorption [15], but 3-10 lM EGCG3″ Me clearly suppressed the bone resorption in the present study. Therefore, the inhibitory potency of EGCG3″Me seems to be slightly stronger than that of EGCG in bone resorption.…”
Section: Discussioncontrasting
confidence: 65%
“…Using a mouse experimental model of periodontitis, we previously showed the potential effects of the green tea catechin EGCG in preventing alveolar bone loss . Here, we showed that EGCG3″Me also prevents alveolar bone loss in mice.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A cross-sectional study reported that consumption of ≥1 cup/day of green tea decreased the odds ratio for tooth loss (Koyama et al, 2010). EGCG inhibits lipopolysaccharide-induced osteoclastic bone resorption in vitro and attenuates inflammatory bone loss of the mouse mandibular alveolar bone in vivo (Tominari et al, 2015). Local delivery of green tea catechin has been used as an effective adjunctive therapy along with scaling and root planing for the treatment of 8 chronic periodontitis (Gadagi, Chava & Reddy, 2013;Hattarki, Pushpa & Bhat, 2013;Hirasawa, Takada, Makimura & Otake, 2002).…”
Section: Introductionmentioning
confidence: 99%